Equality in Distribution of Random Sums for Introducing Selfdecomposability - Artikis, Constantinos T.; Artikis, Panagiotis T. (Communications in Mathematics and Applications, 2020)
It constitutes a general recognition that discrete Poisson random sums are very strong tools of probability theory with significant applications in a very wide variety of important practical disciplines. The paper makes use of an equality in distribution for the investigation of the structure of a particularly significant class of discrete Poisson random sums.